Cyclic loading behavior of a repaired subway station after fire exposure. (February 2019) - Zhao, Huiling; Yu, Haitao; Yuan, Yong; Li, Pan; Chen, Juntao
Highlights: Post fire slab-column/wall underground structure is assessed by pushover cyclic tests. Columns are key members and a catenary mechanism forms after columns shear failure. Fire of 5 MW intensity causes substantial damage to structure, lacking of capacity. Abstract: After a fire, underground concrete structures, specifically in subway stations, are often repaired and reused rather than demolished. The mechanical performances of a structure after being exposed to fire require intensive evaluation before a station is reopened. This paper describes the mechanical behavior of a post-fire subway station structure by means of a structural test. A large-scale slab-column/wall structure was exposed to fire. After one of the columns damaged by fire was repaired, a combination of constant vertical load and cyclic lateral load was applied on the repaired structure. A cyclic pushover test was carried out to discover the mechanical behavior of the post-fire structure under soil pressures and service loads. Damage was accumulated as cyclic loadings increased until the structure failed due to shear crushing of the repaired column. The hysteretic loops of the entire structure were thin, indicating that fire exposure decreased the energy dissipation. Results show that the fire caused substantial damage to the structure, resulting in reduced load bearing capacity, deformation capacity, and seismic resistance.